2006
DOI: 10.1080/00365590500368344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute acid loading on acid–base and calcium metabolism

Abstract: The hypercalciuric and hypercalcaemic responses to loading with non-carbonic acid are more pronounced in recurrent idiopathic calcium stone-formers than in healthy individuals. Acid loading (i.e. protein ingestion) may contribute to disturbed bone metabolism in idiopathic calcium nephrolithiasis as well as calcium stone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This rise in serum calcium was blunted with pharmacological inhibition of cell‐mediated bone resorption (using colchicine or calcitonin), supporting the notion that bone matrix is actively degraded in response to an acid load. A randomized trial by Osther 99 also observed increasing ionized calcium in serum in response to acute acid loading. This effect has been reported in one trial of high protein intake 22 ; however, most studies have not seen a change in serum calcium with high protein intakes 53,66,100 …”
Section: Protein and Bonementioning
confidence: 92%
“…This rise in serum calcium was blunted with pharmacological inhibition of cell‐mediated bone resorption (using colchicine or calcitonin), supporting the notion that bone matrix is actively degraded in response to an acid load. A randomized trial by Osther 99 also observed increasing ionized calcium in serum in response to acute acid loading. This effect has been reported in one trial of high protein intake 22 ; however, most studies have not seen a change in serum calcium with high protein intakes 53,66,100 …”
Section: Protein and Bonementioning
confidence: 92%
“…This acid load unequivocally has been shown to result in increased renal excretion rates of calcium and decreased urinary excretion of citrate. 35 From a pathophysiological point of view, this combination may result in an increased risk of calcium salt crystallization in the urine. In a recent case-control study, 123 renal calcium stone formers were compared with age-and sex-matched controls with regard to the potential renal acid load calculated from dietary records.…”
Section: Dietary Salt and Hypertensionmentioning
confidence: 99%
“…Data in the literature suggest that individuals forming calcium containing stones in the kidney may be more sensitive to such an acid load, potentially tilting the subtle balance in urine toward crystallization. 35 Furthermore, the low urine pH resulting from animal protein loads potentially may increase risk of uric acid stone formation. This may be especially important in individuals with insulin resistance that results in reduced ammoniagenesis and persistent acid urine, which has been shown to be closely associated with uric acid nephrolithiasis.…”
Section: Dietary Salt and Hypertensionmentioning
confidence: 99%
“…This is a risk factor for the development of uric acid stones and may play a role in calcium stone formation. (5) Chronic metabolic acidosis induced by the increased acid load decreases calcium reabsorption within the nephron [8587]. (6) The decreased urinary pH may potentiate uric acid lithiasis, and it enhances citrate reabsorption in the proximal tubules, thus decreasing the excretion of this important inhibitor of crystallization [88].…”
Section: Differences In Epidemiologymentioning
confidence: 99%